Measurement and Evaluation of Low Frequency Electromagnetic Field in Camera Observation Rooms - Bozkurt, İlyas; Pala, Zeydin; Etem, Taha (Institute of Electrical and Electronics Engineers Inc., 2017)
In this study, low frequency electromagnetic field measurements (EMF) were performed in camera observation rooms and work offices at Mus Alparslan University. The electromagnetic measurements of the emitted values were measured with WP400 probe using SMP2 measuring device. The results obtained from different measurement points are compared by graphs. © 2017 IEEE.
13th International Conference Perspective Technologies and Methods in MEMS Design, MEMSTECH 2017 -- 20 April 2017 through 23 April 2017 -- -- 128152
Keywords: Electromagnetic Field; Electromagnetic Pollution; EMF measurements; Low Frequency Electromagnetic Field